Detention in Kenya: risks for refugees and asylum seekers - Kiama, L; Likule, D (Refugee Studies Centre, University of Oxford, 2013)
Refugees and asylum seekers detained in Kenya risk multiple convictions and protracted detention due to poor coordination between immigration officials, police and prison officers, coupled with lack of sufficient interpreters and low levels of knowledge among government officers and law enforcement officers on protection of refugees and asylum seekers